2006
DOI: 10.1107/s0108768106011426
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of selenium and selenium-diiodine analogues of the antithyroid drug 6-n-propyl-2-thiouracil and its alkyl derivatives

Abstract: The structures of four selenium analogues of the antithyroid drug 6-n-propyl-2-thiouracil [systematic name: 2,3-dihydro-6-n-propyl-2-thioxopyrimidin-4(1H)-one], namely 6-methyl-2-selenouracil, C(5)H(6)N(2)OSe (1), 6-ethyl-2-selenouracil, C(6)H(8)N(2)OSe (2), 6-n-propyl-2-selenouracil, C(7)H(10)N(2)OSe (3), and 6-isopropyl-2-selenouracil, C(7)H(10)N(2)OSe (4), are described, along with that of the dichloromethane monosolvate of 6-isopropyl-2-selenouracil, C(7)H(10)N(2)OSe.CH(2)Cl(2) (4.CH(2)Cl(2)). The extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Since then, a large number of such complexes have been studied. This interest has been driven in large part by research in two areas: the unusual electric properties imparted to materials when doped with dihalogens (particularly iodine) [55], and the study of dihalogen and interhalogen complexes with potential antithyroid drugs and related derivatives, including dithiole thiones [56][57][58][59][60][61][62][63][64][65], imidazole thiones [19,[66][67][68][69][70][71][72][73] and selones [68,[74][75][76], thiazole thiones [77] and selones [78][79][80], oxazole thiones [81], and various thiourea derivatives [77,82]. Additional activity has involved the fundamental study of halogen bonding in particular classes of compounds, such as aromatic nitrogen heterocycles [31,[83][84][85][86][87][88][89][90][91][92][93][94]96], thioether...…”
Section: General Observationsmentioning
confidence: 99%
“…Since then, a large number of such complexes have been studied. This interest has been driven in large part by research in two areas: the unusual electric properties imparted to materials when doped with dihalogens (particularly iodine) [55], and the study of dihalogen and interhalogen complexes with potential antithyroid drugs and related derivatives, including dithiole thiones [56][57][58][59][60][61][62][63][64][65], imidazole thiones [19,[66][67][68][69][70][71][72][73] and selones [68,[74][75][76], thiazole thiones [77] and selones [78][79][80], oxazole thiones [81], and various thiourea derivatives [77,82]. Additional activity has involved the fundamental study of halogen bonding in particular classes of compounds, such as aromatic nitrogen heterocycles [31,[83][84][85][86][87][88][89][90][91][92][93][94]96], thioether...…”
Section: General Observationsmentioning
confidence: 99%
“…Dashed lines indicate hydrogen bonds. thiouracil (refcode PELHEU; Antoniadis et al, 2006), the molecules are hydrogen bonded into chains by R 2 2 (8) interactions involving either N-HÁ Á ÁSe or N-HÁ Á ÁO hydrogen bonds. We therefore undertook crystallization experiments with 6-propyl-2-thiouracil alone to study whether similar interactions can be observed.…”
Section: Figurementioning
confidence: 99%
“…The selenium-containing analogues of antithyroid drugs are synthesized, and seems to have some advantages in comparison to their sulfur containing counterparts. 48 , 49 These compounds could be newer antithyroid drug candidates. Since some investigations mentioned a potential role for "sulfur" atom in antithyroid agents to induce toxicity during metabolism, 50 substituting "sulfur" with "selenium" might reduce the risk of antithyroid drugs-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%